A sodium ion secondary battery
By adjusting the specific surface area of the electrolyte components and the negative electrode active substance in a sodium ion secondary battery, a stable membrane structure is formed, which solves the problem of sodium bisfluorosulfonimide corrosion of the current collector, and improves the first effect and cycling performance of the battery , enhancing the conductivity and thermal stability of the electrolyte.
Patent Information
- Application Number
- CN202211074980.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-02
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-09-02
AI Technical Summary
In existing sodium ion secondary batteries, sodium bisfluorosulfonimide corrodes the current collector, reducing the battery cycle performance and low first-term efficiency.
Use a sodium ion secondary battery including a positive electrode, an negative electrode and an electrolyte. The electrolyte contains sodium bisfluorosulfonimide, sulfate compounds and corrosion inhibitors to meet the specific mass percentage content range and specific surface area relationship to form a stable SEI and CEI membranes inhibit battery side reactions and improve battery first-effect and cycling performance.
Effectively reduce battery impedance, reduce irreversible capacity loss, improve battery first-time efficiency and cycling performance, ensure that the current collector does not corrode, and enhance the conductivity and thermal stability of the electrolyte.
Smart Images

Figure GDA0003963178080000121 
Figure GDA0003963178080000131 
Figure GDA0003963178080000141
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion secondary battery. Background Art
[0002] In recent years, with the rapid development of the new energy industry, lithium-ion batteries have also been widely used in the field of new energy vehicles, and the demand for lithium-ion batteries has increased rapidly. With the increase in demand, the cost of lithium resources has continued to increase, and the production cost of lithium-ion batteries has also gradually increased. Faced with the above problems, researchers began to think about using the abundant sodium element to replace the lithium element, and gradually began to study sodium-ion batteries. The principle and structure of sodium-ion batteries are similar to those of lithium-ion batteries. Compared with lithium batteries, sodium-ion batteries have wide resources, low costs and small fluctuations, and have wide temperature ranges and high safety performance, which give them replacement potential. With the continuous advancement of sodium-ion battery technology, sodium-ion batteries will occupy an important position in my country's energy system, especially in the field of energy storage, which has broad growth space. Therefore, the development of high-performance, low-cost sodium-ion batteries is the decisive factor in determining whether they can be industrialized.
[0003] In sodium-ion batteries, the electrolyte using sodium bis(fluorosulfonyl)imide as the main salt can improve the conductivity, electrochemical and thermal stability of the electrolyte. During the battery charge and discharge cycle, too much sodium bis(fluorosulfonyl)imide will corrode the current collector and reduce the battery cycle performance. Currently, the negative electrode material of sodium-ion batteries is mainly biomass hard carbon. However, although the hard carbon calcined at low temperature has higher ionic conductivity, it has the disadvantages of low initial efficiency and unstable cycle. Summary of the invention
[0004] The technical problem to be solved by the present invention is to solve the problem that sodium bis(fluorosulfonyl)imide as the main salt in the electrolyte of sodium ion secondary batteries in the prior art corrodes the current collector, reduces the battery cycle performance, and has low initial efficiency of the battery. The present application provides a sodium ion secondary battery.
[0005] In order to solve the above technical problems, the present application provides a sodium ion secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material, the electrolyte comprises a sodium salt, a non-aqueous organic solvent and an additive, the sodium salt comprises sodium bis(fluorosulfonyl)imide, and the additive corrosion inhibitor comprises a corrosion inhibitor and a sulfate compound;
[0006] The sodium ion secondary battery satisfies the following relationship:
[0007] 0.4≤(a·d) / (b·c)≤23,
[0008] Wherein, 3≤a≤15, 0.5≤b≤3, 3≤c≤7, 0.5≤d≤15, and the mass percentage of sodium bis(fluorosulfonyl)imide in the electrolyte is a%;
[0009] The mass percentage of the sulfate ester compound in the electrolyte is b%;
[0010] The specific surface area of the negative electrode active material is c, in m 2 / g;
[0011] The mass percentage of the corrosion inhibitor in the electrolyte is d%.
[0012] Preferably, the sodium ion secondary battery satisfies the following relationship:
[0013] 0.5≤(a·d) / (b·c)≤15.
[0014] Preferably, the range of a is 4≤a≤13.
[0015] Preferably, the sulfate compound comprises a cyclic sulfate, and the cyclic sulfate comprises one or more of 1,3-propane sultone, 1,3-propene sultone, vinyl sulfate, propylene sulfate, dimethyl sulfate, 4-methylethylene sulfate, 4-propylethylene sulfate, propylene sulfate, 4-methylpropylene sulfate and 4-propylpropylene sulfate;
[0016] The range of b is 1≤b≤3.
[0017] Preferably, the negative electrode active material includes one or more of soft carbon, hard carbon, carbon nanotubes, expanded graphite, and graphene;
[0018] The specific surface area c of the negative electrode active material is in the range of 4≤c≤6.
[0019] Preferably, the corrosion inhibitor comprises one or more of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethylsulfonate (NaSO3CF3), sodium difluorooxalatoborate (NaDFOB) and sodium bis(trifluoromethylsulfonyl)imide (Na[(CF3SO2)2N]);
[0020] The range of d is 3≤d≤12.
[0021] Preferably, the non-aqueous organic solvent includes one or more of carbonates, carboxylates, and ethers;
[0022] The carbonates include cyclic or chain carbonates with 3 to 5 carbon atoms, the cyclic carbonates include one or more of ethylene carbonate, vinylene carbonate, vinylethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonates include one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate;
[0023] The carboxylic acid esters include carboxylic acid esters having 2 to 6 carbon atoms, and the carboxylic acid esters include one or more of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and propyl propionate;
[0024] The ethers include cyclic ethers or chain ethers having 4 to 10 carbon atoms, the cyclic ethers include one or more of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ethers include one or more of dimethoxymethane, 1,2-dimethoxyethane, and diethylene glycol dimethyl ether;
[0025] Taking the mass of the electrolyte as 100%, the mass percentage of the non-aqueous organic solvent is 70% to 92%.
[0026] Preferably, the additive further comprises an auxiliary additive, the auxiliary additive comprises a fluorocarbonate, and the fluorocarbonate comprises one or more of fluoroethylene carbonate or difluoroethylene carbonate;
[0027] Taking the mass of the electrolyte as 100%, the mass percentage of the fluorocarbonate is 1% to 5%.
[0028] Preferably, the positive electrode comprises a positive electrode active material, and the positive electrode active material comprises one or more of a sodium-containing layered oxide, a sodium-containing polyanion compound or a sodium-containing Prussian blue compound;
[0029] The sodium-containing layered oxide comprises a layered transition metal oxide, and the layered transition metal oxide comprises one or more of the compounds shown in Formula I;
[0030] Na x M y O z Formula I
[0031] Wherein, 0<x≤1, 0<y≤1, 1<z≤2, M is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V;
[0032] The Prussian blue compound includes one or more compounds shown in formula II;
[0033] Na x′ L y′[L′(CN)6] y′ ·z′H2O Formula II Wherein, 0<x′≤2, 0<y′≤1, 0<z′≤20,
[0034] L and L' are each selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V;
[0035] The polyanion compound includes a phosphate compound or a sulfate compound;
[0036] The phosphate compound includes one or more compounds represented by formula III or formula IV;
[0037] Na3(M′O 1-q PO4)2F 1+2q Formula III
[0038] Wherein, in 0, the compound, M′ is selected from one or more of Al, V, Ge, Fe, Ga;
[0039] Na2EPO4F Formula IV wherein E is selected from one or more of Fe, Mn;
[0040] The sulfate compound includes one or more compounds represented by formula V;
[0041] Na2Y(SO4)2·2H2O Formula Ⅴ
[0042] Among them, Y is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.
[0043] Preferably, the layered transition metal oxide comprises NaNi m Fe n Mn p O2 compounds, NaNi m Co n Mn p One or more of O2 compounds, wherein m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1;
[0044] The Prussian blue compound includes Na x′ Mn[Fe(CN)6] y′ ·z′H2O compounds, Na x′ Fe[Fe(CN)6] y′ · one or more of z′H2O compounds, wherein 0<x′≤2, 0<y′≤1, 0<z′≤20;
[0045] The phosphate compounds include Na3(VPO4)2F3, Na3(VOPO4)2F, Na2FePO4F, and Na2MnPO4F.
[0046] Beneficial effects:
[0047] Compared with the prior art, the sodium ion secondary battery provided by the present application satisfies the relationship 0.4≤(a·d) / (b·c)≤23, and at the same time satisfies the mass percentage a% of sodium bis(fluorosulfonyl)imide in the electrolyte in the range of 3% to 15%, the mass percentage b% of the sulfate compound in the electrolyte in the range of 0.5% to 3%, and the specific surface area c of the negative electrode active material in the range of 3m 2 / g~7m 2 / g range, the mass percentage d% of the corrosion inhibitor in the electrolyte is in the range of 0.5% to 15%, the electrolyte has a high electrical conductivity, can form a stable CEI film on the positive electrode surface, a stable SEI film on the negative electrode surface, the current collector is not corroded, the occurrence of battery side reactions is inhibited, the battery impedance is effectively reduced, the irreversible capacity loss is reduced, and the battery initial efficiency and cycle performance are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a metallographic microscope image of the current collector of the battery of Comparative Example 9 after 200 cycles;
[0049] Figure 2 This is a scanning electron microscope image of the current collector of Example 9 after the battery was cycled for 200 weeks. DETAILED DESCRIPTION
[0050] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] The present application provides a sodium ion secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material, the electrolyte comprises a sodium salt, a non-aqueous organic solvent and an additive, the sodium salt comprises sodium bis(fluorosulfonyl)imide, and the additive corrosion inhibitor comprises a corrosion inhibitor and a sulfate compound;
[0052] The sodium ion secondary battery satisfies the following relationship:
[0053] 0.4≤(a·d) / (b·c)≤23,
[0054] Among them, 3≤a≤15, 0.5≤b≤3, 3≤c≤7, 0.5≤d≤15,
[0055] The mass percentage of sodium bis(fluorosulfonyl)imide in the electrolyte is a%;
[0056] The mass percentage of the sulfate ester compound in the electrolyte is b%;
[0057] The specific surface area of the negative electrode active material is c, in m 2 / g;
[0058] The mass percentage of the corrosion inhibitor in the electrolyte is d%.
[0059] The inventors have found through extensive research that adding 3% to 15% by weight of sodium bis(fluorosulfonyl)imide to the electrolyte can reduce the corrosion risk of the current collector at its low concentration. At the same time, combined with 0.5% to 15% by weight of corrosion inhibitor, it can ensure the long cycle of the battery during the battery cycle while also inhibiting the occurrence of current collector corrosion; adding 0.5% to 3% by weight of sulfate compounds can inhibit the side reactions of the battery in the formation stage, reduce the irreversible capacity loss of the battery, and achieve the effect of improving the first cycle efficiency of the battery; limiting the specific surface area of the negative electrode active material to 3 to 7 m 2 / g, reducing the consumption of electrolyte, ensuring sufficient platform capacity of the hard carbon negative electrode, and ensuring the full utilization of the battery capacity; at the same time, the sodium ion secondary battery provided by the present application satisfies the relationship 0.4≤(a·d) / (b·c)≤23, can form a stable CEI film on the positive electrode surface and a stable SEI film on the negative electrode surface, the current collector is not corroded, the occurrence of battery side reactions is inhibited, the battery impedance is effectively reduced, the irreversible capacity loss is reduced, and the battery initial efficiency and cycle performance are improved.
[0060] The mass percentage of sodium bis(fluorosulfonyl)imide added to the electrolyte is a%, and the range of a% is 3%≤a%≤15%; for example, the mass percentage of sodium bis(fluorosulfonyl)imide can be 3%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%.
[0061] In some preferred embodiments, the mass percentage of sodium bis(fluorosulfonyl)imide is a%, and the range of a% is 4%≤a%≤13%.
[0062] Specifically, if a is greater than 15, the viscosity of the electrolyte increases, affecting the sodium ion transfer rate, increasing polarization, and increasing battery impedance; during the battery cycle, the content of sodium bis(fluorosulfonyl)imide increases, corroding the current collector, and the active material coated on the surface of the current collector falls off, seriously deteriorating the battery cycle performance. If a is less than 3, the conductivity of the electrolyte decreases, the internal resistance of the battery increases, and the formation of the SEI film on the negative electrode surface is affected. The mass percentage of sodium bis(fluorosulfonyl)imide added to the electrolyte is in the range of 3 to 15%, which can improve the conductivity, electrochemical properties and thermal stability of the electrolyte; it participates in the formation of the SEI film on the negative electrode surface during the battery cycle, reduces side reactions, effectively reduces the impedance during the battery cycle, and improves the battery cycle performance.
[0063] The mass percentage of the sulfate ester compound added to the electrolyte is b%, and the range of b% is 0.5%≤b%≤3%; for example, the mass percentage of the sulfate ester compound can be 0.5%, 0.8%, 1.0%, 1.4%, 1.5%, 1.8%, 2.0%, 2.3%, 2.5%, 2.8%, and 3.0%.
[0064] In some preferred embodiments, the mass percentage of the sulfate ester compound added to the electrolyte is b%, and the range of b% is 1%≤b%≤3%.
[0065] Specifically, if b is greater than 3, during the battery reaction, the additive excessively participates in the film formation, the film thickness on the surface of the electrode material increases, the side reactions of the battery in the formation stage increase, the battery impedance increases, and the battery's first efficiency and cycle performance decrease. If b is less than 0.5, the film formation effect is poor, the CEI film and SEI film are thin, and the battery's cycle performance deteriorates. When the mass content of sulfate ester compounds added to the electrolyte is in the range of 0.5% to 3%, the sulfate ester compounds participate in the electrode film formation, which can inhibit the side reactions of the battery in the formation stage, reduce irreversible capacity loss, and improve the battery's first efficiency and cycle performance.
[0066] The mass percentage of the corrosion inhibitor in the electrolyte is d%, and the range of d% is 0.5%≤d%≤15%. For example, the mass percentage of the corrosion inhibitor can be 0.5%, 1.0%, 2.4%, 3.0%, 3.9%, 4.3%, 5.4%, 6.0%, 6.5%, 6.8%, 7.0%, 7.8%, 8.0%, 8.5%, 9.0%, 10.0%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13.0%, 14.0%, 15.0%.
[0067] In some preferred embodiments, the mass percentage of the corrosion inhibitor in the electrolyte is d%, and the range of d% is 3%≤d%≤12%.
[0068] Specifically, when d is greater than 15, the content of the corrosion inhibitor is high, the proportion of the solvent is reduced, the viscosity of the electrolyte is too large, the sodium salt is difficult to dissolve, the sodium ion migration rate is reduced, the battery impedance increases, and the battery cycle performance is reduced. When d is less than 0.5, the current collector is easily corroded during the battery cycle, and the battery cycle performance is reduced. The mass content of the corrosion inhibitor in the electrolyte is between 0.5% and 15%, which effectively inhibits the corrosion of the current collector, and cooperates with the mass content of sodium bis(fluorosulfonyl)imide between 3% and 15%. Under the condition of a lower content of sodium bis(fluorosulfonyl)imide, the occurrence of current collector corrosion can be inhibited while ensuring the long cycle of the battery.
[0069] In some preferred embodiments, the sodium ion secondary battery satisfies the following relationship: 0.5≤(a·d) / (b·c)≤15.
[0070] Specifically, the sodium ion secondary battery satisfies the relationship within the range of 0.5≤(a·d) / (b·c)≤15, the electrolyte has a higher conductivity, and it is easier to form a stable SEI film and CEI film on the electrode surface, and the prepared battery has a higher first efficiency and cycle performance.
[0071] In some embodiments, the sulfate ester compound includes a cyclic sulfate ester, and the cyclic sulfate ester includes one or more of 1,3-propane sultone, 1,3-propene sultone, vinyl sulfate, propylene sulfate, dimethyl sulfate, 4-methylethylene sulfate, 4-propylethylene sulfate, propylene sulfate, 4-methylpropylene sulfate and 4-propylpropylene sulfate.
[0072] In some preferred embodiments, the sulfate ester compound is vinyl sulfate.
[0073] In some preferred embodiments, the sulfate ester compound is 1,3-propylene sultone
[0074] In some preferred embodiments, the vinyl sulfate consists of vinyl sulfate and 1,3-propene sultone.
[0075] In some embodiments, the negative electrode active material includes one or more of soft carbon, hard carbon, carbon nanotubes, expanded graphite, graphene, non-metals such as phosphorus, metal foils such as aluminum, tin, antimony, or alloy compounds.
[0076] In some embodiments, the corrosion inhibitor includes one or more of sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium trifluoroacetate (CF3COONa), sodium tetraphenylborate (NaB(C6H5)4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium difluorooxalatoborate (NaDFOB) and sodium bis(trifluoromethylsulfonyl)imide (Na[(CF3SO2)2N]).
[0077] In some embodiments, the non-aqueous organic solvent includes one or more of carbonates, carboxylates, and ethers;
[0078] Preferably, the carbonates include cyclic carbonates or chain carbonates having 3 to 5 carbon atoms, wherein the cyclic carbonates include but are not limited to one or more of ethylene carbonate (EC), vinylene carbonate (VC), vinylethylene carbonate (VEC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonates may specifically be but are not limited to one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC);
[0079] Preferably, the carboxylate solvent includes carboxylate with carbon number of 2 to 6, and the carboxylate includes but is not limited to one or more of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, and propyl propionate (PP).
[0080] As a preferred solution, the sodium ion secondary battery electrolyte further includes vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate (FEC);
[0081] Preferably, the ether solvent includes a cyclic ether or a chain ether having 4 to 10 carbon atoms, wherein the cyclic ether includes but is not limited to one or more of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether includes but is not limited to one or more of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), and diethylene glycol dimethyl ether (TEGDME).
[0082] Taking the mass of the electrolyte as 100%, the mass percentage of the non-aqueous organic solvent is 70% to 92%.
[0083] Non-aqueous organic solvents dissolve sodium salts, additives and auxiliary additives. If the content of non-aqueous organic solvents is lower than 70%, the solubility of sodium salts decreases, the viscosity of the electrolyte increases, and the battery impedance increases. If the content of non-aqueous organic solvents is higher than 92%, the proportion of additives and auxiliary additives decreases, affecting the film-forming reaction of the additives, the thickness of the film on the surface of the electrode material is thin, and the cycle performance of the battery is reduced.
[0084] In some embodiments, the additive further comprises an auxiliary additive, the auxiliary additive comprises a fluorocarbonate, the fluorocarbonate comprises fluoroethylene carbonate (FEC) or bisfluoroethylene carbonate (DFEC);
[0085] Taking the mass of the electrolyte as 100%, the mass percentage of the fluorocarbonate is 1% to 5%.
[0086] Specifically, the mass percentage of the fluorocarbonate added to the electrolyte can be 1%, 1.5%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, or 5.0%, as long as the mass percentage of the fluorocarbonate added is between 1% and 5%.
[0087] In some embodiments, the positive electrode includes a positive electrode active material, and the positive electrode active material includes one or more of a sodium-containing layered oxide, a sodium-containing polyanion compound, or a sodium-containing Prussian blue compound;
[0088] The sodium-containing layered oxide comprises a layered transition metal oxide, and the layered transition metal oxide comprises one or more of the compounds shown in Formula I;
[0089] Na x M y O z Formula I
[0090] Wherein, 0<x≤1, 0<y≤1, 1<z≤2, M is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V;
[0091] The Prussian blue compound includes one or more compounds shown in formula II;
[0092] Na x′ L y′ [L′(CN)6] y′ ·z′H2O Formula Ⅱ
[0093] Wherein, 0<x′≤2, 0<y′≤1, 0<z′≤20, L and L′ are each selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V;
[0094] The polyanion compound includes a phosphate compound or a sulfate compound;
[0095] The phosphate compound includes one or more compounds represented by formula III or formula IV;
[0096] Na3(M′O 1-q PO4)2F 1+2q Formula III
[0097] Wherein, in 0, the compound, M′ is selected from one or more of Al, V, Ge, Fe, Ga;
[0098] Na2EPO4F Formula IV wherein E is selected from one or more of Fe, Mn;
[0099] The sulfate compound includes one or more compounds represented by formula V;
[0100] Na2Y(SO4)2·2H2O Formula Ⅴ
[0101] Among them, Y is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.
[0102] In some preferred embodiments, the layered transition metal oxide comprises NaNi m Fe n Mn p O2 compounds, NaNi m Co n Mn p One or more of O2 compounds, wherein m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1;
[0103] The Prussian blue compound includes Na x′ Mn[Fe(CN)6] y′ ·z′H2O compounds, Na x′ Fe[Fe(CN)6] y′ · one or more of z′H2O compounds, wherein 0<x′≤2, 0<y′≤1, 0<z′≤20;
[0104] The phosphate compounds include Na3(VPO4)2F3, Na3(VOPO4)2F, Na2FePO4F, and Na2MnPO4F.
[0105] On the other hand, the present application provides a method for preparing a sodium ion secondary battery, comprising the following steps: preparation of a positive electrode: uniformly mixing a positive electrode active material, a binder, a conductive agent, and a solvent, coating the mixture on a substrate, and removing the solvent to obtain a positive electrode;
[0106] Preparation of negative electrode: the negative electrode active material, binder, conductive agent and solvent are uniformly mixed, coated on a substrate, and the solvent is removed to obtain a negative electrode;
[0107] Preparation of electrolyte: uniformly mixing sodium salt, additives and non-aqueous organic solvent to obtain electrolyte, wherein the additives include sulfate compounds and corrosion inhibitors, and the sodium salt includes sodium bis(fluorosulfonyl)imide;
[0108] The positive electrode, the negative electrode and the electrolyte are assembled to obtain a sodium ion secondary battery.
[0109] The prepared sodium ion secondary battery satisfies the following relationship: 0.4≤(a·d) / (b·c)≤23, wherein 3≤a≤15, 0.5≤b≤3, 3≤c≤7, 0.5≤d≤15, and the mass percentage of sodium bis(fluorosulfonyl)imide in the electrolyte is a%;
[0110] The mass percentage of the sulfate ester compound in the electrolyte is b%;
[0111] The specific surface area of the negative electrode active material is c, in m 2 / g;
[0112] The mass percentage of the corrosion inhibitor in the electrolyte is d%.
[0113] In some embodiments, the positive electrode further includes a positive electrode current collector, and the positive electrode material layer is disposed on a surface of the positive electrode current collector.
[0114] The positive electrode current collector is selected from a metal material that can conduct electrons. Preferably, the positive electrode current collector includes one or more of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0115] In some embodiments, the positive electrode includes a positive electrode active material layer, and the positive electrode material layer also includes a positive electrode binder and a positive electrode conductor. The positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.
[0116] The positive electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.
[0117] The positive electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0118] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer is disposed on the surface of the negative electrode current collector. The material of the negative electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail herein.
[0119] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are mixed to obtain the negative electrode material layer. The negative electrode binder and the negative electrode conductive agent may be the same as the positive electrode binder and the positive electrode conductive agent, respectively, and will not be described in detail here.
[0120] In some embodiments, the solvent includes N-methylpyrrolidone, deionized water, acetone, propanol, ethanol, and the like.
[0121] In some embodiments, the secondary battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.
[0122] The diaphragm may be an existing conventional diaphragm, which may be a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0123] The specific embodiments of the present invention will be further explained below through examples, but it does not mean that the protection scope of the present invention is limited to the scope described in the examples.
[0124] Example 1
[0125] This embodiment is used to illustrate the sodium ion secondary battery disclosed in this application.
[0126] The components in the electrolyte are as follows: based on 100% of the electrolyte, the mass content of the non-aqueous organic solvent is 82.5%, wherein the mass ratio of the non-aqueous organic solvent is EC, PC, and EMC is 20:10:70; the additives are selected from fluoroethylene carbonate (FEC) with a mass content of 2%, cyclic sulfate compounds including 1,3-propylene sultone (RPS) with a mass content of 1%, and vinyl sulfate (DTD) with a mass content of 1%; the mass content of the corrosion inhibitor sodium hexafluorophosphate (NaPF6) is 0.5%; the mass content of the sodium salt sodium bis(fluorosulfonyl)imide (NaFSI) is 13%.
[0127] Preparation of electrolyte: Add the above-mentioned non-aqueous organic solvent, additives and sodium salt into a stirring container and mix them evenly to prepare the electrolyte.
[0128] The preparation of a sodium ion secondary battery comprises the following steps:
[0129] (1) Preparation of positive electrode: The positive electrode active material (Na 1.2 Ni2[Fe(CN)6] 0.5 H2O, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) are mixed and then dispersed in a proper amount of N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry; the obtained slurry is evenly coated on both sides of aluminum foil, dried, rolled and vacuum dried, and aluminum lead wires are welded with an ultrasonic welder to obtain a positive electrode plate, and the thickness of the plate is between 120-150μm.
[0130] (2) Preparation of negative electrode: According to the mass ratio of 94:1:2.5:2.5, the specific surface area of the negative electrode active material is 5m 2 / g of hard carbon, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed, and then dispersed in an appropriate amount of deionized water to obtain a negative electrode slurry; the slurry is coated on both sides of a copper foil, and after drying, calendering and vacuum drying, a nickel lead wire is welded with an ultrasonic welder to obtain a negative electrode plate, and the thickness of the plate is between 120-150μm.
[0131] (3) Preparation of sodium ion secondary battery: A three-layer separator with a thickness of 20 μm was placed between the positive electrode plate and the negative electrode plate prepared above, and then the sandwich structure consisting of the positive electrode plate, the negative electrode plate and the separator was wound, and then the wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid. In a glove box with a dew point controlled below -40°C, the electrolyte prepared above was injected into the battery cell, vacuum-sealed, and left to stand for 24 hours.
[0132] Example 2-13
[0133] The difference between Examples 2-13, Comparative Examples 1-3, 5-12, and Example 1 is that the mass percentages of the cyclic sulfate compound, sodium bis(fluorosulfonyl)imide, and sodium hexafluorophosphate in the electrolyte are different, and the mass percentages of the corresponding non-aqueous organic solvents are adjusted accordingly; the specific surface area of the negative electrode active material is different, and the rest is the same as Example 1, as shown in Table 1 below.
[0134] Examples 17-18
[0135] The type of corrosion inhibitor in Example 17 is different from that in Example 3, and the rest is the same as that in Example 3, as shown in Table 1 below. The type of corrosion inhibitor in Example 18 is different from that in Example 7, and the rest is the same as that in Example 7, as shown in Table 1 below.
[0136] Examples 19-23
[0137] The types of sulfate compound additives in Examples 19-23 are different from those in Examples 6-9 and 10-11, and the rest of the preparation methods are the same, as shown in Table 1 below.
[0138] Table 1 Electrolyte and battery parameters of Examples 1-23 and Comparative Examples 1-13
[0139]
[0140]
[0141] Sodium ion secondary battery corrosion performance test:
[0142] Analysis of aluminum current collector corrosion:
[0143] The batteries prepared in Example 3 and Comparative Examples 1, 9, 11 and Comparative Example 7 were charged at a constant current of 1C and a constant voltage of 4.2V, and then charged at 0.03C and discharged at 1C / 1.5V. Afterwards, the batteries were cycled 50 times and 200 times respectively according to the above-mentioned charge and discharge conditions to evaluate the effect of the sodium ion battery on inhibiting NaFSI corrosion of the aluminum current collector, as shown in Table 2 below.
[0144] Corrosion area ratio: The battery after 200 cycles was observed using a metallographic microscope and a scanning electron microscope to determine the ratio of the corroded area to the entire current collector area.
[0145] Figure 1 This is a metallographic microscope image of the current collector of the battery in comparative example 9 after 200 cycles. Figure 2 This is a scanning electron microscope image of the current collector of Example 9 after the battery was cycled 200 times.
[0146] Battery performance test:
[0147] (1) First effect:
[0148] At room temperature, the batteries prepared in Examples 1-23 and Comparative Examples 1-13 were charged to 3.9V at 0.2C, and then the constant voltage charging current was reduced to 0.02C to test the initial capacity C0 of the battery, and then discharged to 1.5V at a constant current of 0.2C to obtain the discharge capacity C1 of the battery;
[0149] First effect = C1 / C0×100%.
[0150] (2) 25℃ normal temperature cycle test:
[0151] The batteries prepared in Examples 1-23 and Comparative Examples 1-13 were placed at a room temperature of 25° C., charged at a constant current of 0.7C to 3.9V, then charged at a constant voltage of 3.9V, with a cut-off current of 0.05C, and then discharged at a constant current of 1C to 1.5V, and this cycle was repeated for 200 cycles;
[0152] The 200-cycle capacity retention rate was calculated as follows: discharge capacity at the 200th cycle / average discharge capacity at the 1st to 3rd cycle × 100%.
[0153] (3) 45℃ high temperature cycle test:
[0154] The batteries prepared in Examples 1-23 and Comparative Examples 1-13 were placed under high temperature conditions of 45°C, charged at a constant current of 0.7C to 3.9V, then the constant voltage charging current was reduced to 0.02C, and then discharged at a constant current of 1C to 1.5V, and this cycle was repeated for 200 weeks; the discharge capacity at the first week and the discharge capacity at the 200th week were recorded.
[0155] The 200-cycle capacity retention rate was calculated as follows: discharge capacity at the 200th cycle / discharge capacity at the 1st cycle×100%.
[0156] The electrical performance test data are shown in Table 3.
[0157] Table 2 Battery corrosion performance test data of Example 3 and Comparative Examples 1, 9, 11, 7
[0158]
[0159] It can be seen from Table 1 and Table 2 that, by comparing Example 3, Comparative Examples 1, 9, and 11, adding an anti-corrosion additive to the electrolyte can inhibit the corrosion of the current collector; when the mass content of sodium bis(fluorosulfonyl)imide added in Comparative Example 7 exceeds the range of 3% to 15%, the corrosion area of the aluminum foil increases significantly, and the number of corrosion points increases, indicating that when the mass fraction of NaFSI exceeds the range of 3% to 15%, the anti-corrosion additive (NaDFOB) cannot effectively inhibit corrosion, indicating that the content of sodium bis(fluorosulfonyl)imide is between 3% and 15%, and the synergistic mass percentage of the corrosion inhibitor is between 0.5 and 15%, which can prevent the corrosion of the battery current collector, thereby improving the battery's cycle capacity retention rate.
[0160] Table 3 Battery performance test data of Examples 1-23 and Comparative Examples 1-13
[0161]
[0162]
[0163] It can be seen from Tables 1-3 that, in comparison between Example 3 and Comparative Examples 1-3, no sulfate compound was added to the electrolyte of Comparative Example 1, and the first efficiency and cycle capacity retention rate of the battery were much lower than those of Example 3; a small amount of vinyl sulfate was added to Comparative Example 3, and the first efficiency and cycle capacity retention rate of the battery were slightly improved; in Comparative Example 2, the amount of sulfate compound added was further increased, and the first efficiency of the battery was lower than that of Comparative Example 3. It is speculated that adding sulfate compound content between 0.5% and 3.0% to the electrolyte can inhibit the side reactions of the battery in the formation stage and improve the first efficiency of the battery. Comparative Examples 2 and 3 are compared with Comparative Examples 4-5. Comparative Example 4 increases the specific surface area c of the negative electrode active material, and the first efficiency and cycle capacity retention rate of the battery decrease by more than 10%. The specific surface area of the negative electrode active material added to the battery in Comparative Example 5 is less than 3m 2 / g, the battery's first efficiency and cycle capacity retention rate are slightly lower, and it is inferred that the specific surface area of the negative electrode active material is higher than 7m 2 / g, the difficulty of electrolyte infiltration into the negative electrode increases, which is not conducive to the formation of a stable SEI film on the negative electrode surface, and the cycle capacity retention rate is greatly reduced; the specific surface area of the negative electrode active material is lower than 3m 2 / g, which affects the formation of a stable SEI film by sodium bis(fluorosulfonyl)imide, sulfate compounds, and corrosion inhibitors on the surface of the negative electrode material, and reduces the battery's first efficiency and capacity retention rate. Compared with Examples 6-8, Examples 3 and 4 show that there is no main salt in Comparative Example 6, and effective charge and discharge tests cannot be performed. A small amount of sodium bis(fluorosulfonyl)imide is added to Comparative Example 8. It is speculated that the content of sodium bis(fluorosulfonyl)imide is too low, the conductivity of the electrolyte is low, the stability of the SEI film on the negative electrode surface is poor, and the battery's first efficiency and cycle retention rate are low; the content of sodium bis(fluorosulfonyl)imide added in Comparative Example 7 is too high, the viscosity of the electrolyte increases, the polarization increases, and the corrosion points of the aluminum foil increase, which seriously affects the battery's cycle capacity retention rate. In Example 3 compared with Comparative Example 9, there is no corrosion inhibitor in the electrolyte, the aluminum foil current collector not only increases corrosion, but also the battery cycle capacity retention rate is poor. The corrosion inhibitor added in Comparative Example 10 is greater than 15%. It is speculated that the viscosity of the electrolyte is too large, the sodium salt is difficult to dissolve, and the sodium ion migration rate is reduced, thereby reducing the battery cycle capacity retention rate; it shows that if there is no corrosion inhibitor in the electrolyte, the current collector is easy to be corroded. Adding corrosion inhibitors between 0.5% and 15% in the electrolyte is easy to dissolve sodium salts, ensure the sodium ion migration rate, and improve the battery cycle capacity retention rate. In Example 3 compared with Comparative Example 11, there is no corrosion inhibitor and sulfate compound in the electrolyte of Comparative Example 11, the corrosion area of the positive electrode current collector is close to 50%, and the cycle capacity retention rate and first effect are worse than those of Comparative Example 9, indicating that sulfate compounds and corrosion inhibitors are not added to the electrolyte, and the battery cycle capacity retention rate and first effect are worse. It is speculated that adding sulfate compounds and corrosion inhibitors to the electrolyte has the effect of synergistically improving the battery cycle capacity retention rate and first effect.
[0164] Compared with Comparative Examples 12-13, a, b, c, and d added to the electrolyte in Examples 1-23 are all within the scope of the present application, but the battery does not satisfy the relationship 0.4≤(a·d) / (b·c)≤23, and the first efficiency and cycle capacity retention rates of the battery are lower than those in Examples 1-23, indicating that a, b, c, and d in the electrolyte not only need to satisfy the ranges of 3≤a≤15, 0.5≤b≤3, 3≤c≤7, and 0.5≤d≤15, but the battery also needs to satisfy the relationship 0.4≤(a·d) / (b·c)≤23 in order to form a stable CEI film on the positive electrode surface and a stable SEI film on the negative electrode surface, the current collector is not corroded, the occurrence of battery side reactions is suppressed, the battery impedance is effectively reduced, the irreversible capacity loss is reduced, and the battery first efficiency and cycle performance are improved.
[0165] It can be seen from Examples 1-16 and Examples 17-18 that adding different corrosion inhibitors to the electrolyte has the same effect of improving the battery's cycle capacity retention rate; it can be seen from Examples 1-16 and Examples 19-23 that adding different sulfate ester compounds to the electrolyte has the same effect of improving the battery's first efficiency; this shows that the sulfate ester compounds and corrosion inhibitors of the present application have the same effect of improving the battery's first efficiency and cycle capacity retention rate.
[0166] First efficiency test performance of batteries at different rates
[0167] 1) Initial efficiency test: At room temperature, the prepared sodium ion secondary battery was charged to 3.9V at 0.2C, and then the constant voltage charging current was reduced to 0.02C to test the initial capacity C0 of the battery, and then the battery was discharged to 1.5V at a constant current of 0.2C to obtain the discharge capacity C1 of the battery;
[0168] First effect = C1 / C0×100%.
[0169] The electrolytes prepared according to Example 3 and Comparative Examples 7, 9, and 11 were prepared into sodium ion secondary batteries, and then discharged at constant currents of 0.2C, 0.5C, 1C, 2C, and 3C, respectively, to test the initial efficiency of the batteries at different discharge rates. The test results are shown in Table 4 below.
[0170] Table 4: First efficiency data of batteries in Example 3 and Comparative Examples 7, 9, and 11 at different rates
[0171]
[0172] As shown in Table 4, by adding sulfate ester compounds into the electrolyte, the battery has a higher first effect at different rates. It is speculated that the sulfate ester compounds in the electrolyte have the effect of inhibiting the side reactions of the battery in the formation stage, reducing the irreversible capacity loss of the battery, and improving the first effect of the battery.
[0173] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A sodium ion secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material, the electrolyte comprises a sodium salt, a non-aqueous organic solvent and an additive, the sodium salt comprises sodium bis(fluorosulfonyl)imide, and the additive comprises a corrosion inhibitor and a sulfate compound; The sodium ion secondary battery satisfies the following relationship: 0.4≤(a·d) / (b·c)≤23, Among them, 3≤a≤15, 0.5≤b≤3, 3≤c≤7, 0.5≤d≤15, The mass percentage of sodium bis(fluorosulfonyl)imide in the electrolyte is a%; The mass percentage of the sulfate compound in the electrolyte is b%; The specific surface area of the negative electrode active material is c, in m 2 / g; The mass percentage of the corrosion inhibitor in the electrolyte is d%.
2. The sodium ion secondary battery according to claim 1, characterized in that: The sodium ion secondary battery satisfies the following relationship: 0.5≤(a·d) / (b·c)≤15.
3. The sodium ion secondary battery according to claim 1, characterized in that: The range of a is 4≤a≤13.
4. The sodium ion secondary battery according to claim 1, characterized in that: The sulfate compound includes a cyclic sulfate, and the cyclic sulfate includes one or more of 1,3-propane sultone, 1,3-propene sultone, vinyl sulfate, propylene sulfate, dimethyl sulfate, 4-methylethylene sulfate, 4-propylethylene sulfate, propylene sulfate, 4-methylpropylene sulfate and 4-propylpropylene sulfate; The range of b is 1≤b≤3.
5. The sodium ion secondary battery according to claim 1, characterized in that: The negative electrode active material includes one or more of soft carbon, hard carbon, carbon nanotubes, expanded graphite, and graphene; The specific surface area c of the negative electrode active material is in the range of 4≤c≤6.
6. The sodium ion secondary battery according to claim 1, characterized in that: The corrosion inhibitor includes one or more of sodium perchlorate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoroacetate, sodium tetraphenylborate, sodium trifluoromethanesulfonate, sodium difluorooxalatoborate and sodium bistrifluoromethanesulfonimide; The range of d is 3≤d≤12.
7. The sodium ion secondary battery according to claim 1, characterized in that: The non-aqueous organic solvent includes one or more of carbonates, carboxylates, and ethers; Preferably, the carbonates include cyclic or chain carbonates having 3 to 5 carbon atoms, the cyclic carbonates include one or more of ethylene carbonate, vinylene carbonate, vinylethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonates include one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate; The carboxylic acid esters include carboxylic acid esters having 2 to 6 carbon atoms, and the carboxylic acid esters include one or more of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and propyl propionate; The ethers include cyclic ethers or chain ethers having 4 to 10 carbon atoms, the cyclic ethers include one or more of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ethers include one or more of dimethoxymethane, 1,2-dimethoxyethane, and diethylene glycol dimethyl ether; Taking the mass of the electrolyte as 100%, the mass percentage of the non-aqueous organic solvent is 70% to 92%.
8. The sodium ion secondary battery according to claim 1, characterized in that: The additive further comprises an auxiliary additive, wherein the auxiliary additive comprises a fluorocarbonate, and the fluorocarbonate comprises one or more of fluoroethylene carbonate or difluoroethylene carbonate; Taking the mass of the electrolyte as 100%, the mass percentage of the fluorocarbonate is 1% to 5%.
9. The sodium ion secondary battery according to claim 1, characterized in that: The positive electrode includes a positive electrode active material, and the positive electrode active material includes one or more of a sodium-containing layered oxide, a sodium-containing polyanion compound, or a sodium-containing Prussian blue compound; The sodium-containing layered oxide comprises a layered transition metal oxide, and the layered transition metal oxide comprises one or more of the compounds shown in Formula I; Na x M y O z Formula Ⅰ Wherein, 0<x≤1, 0<y≤1, 1<z≤2, M is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V; The Prussian blue compound includes one or more compounds shown in formula II; Na x´ L y´ [L´(CN)6] y´ •z´H2O Formula II Wherein, 0<x´≤2, 0<y´≤1, 0<z´≤20, L and L´ are each selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V; The polyanion compound includes a phosphate compound or a sulfate compound; The phosphate compound includes one or more compounds represented by formula III or formula IV; Na3(M´O 1-q PO4)2F 1+2q Formula III Wherein, q≤0, M´ is selected from one or more of Al, V, Ge, Fe, and Ga; Na2EPO4F Formula Ⅳ Wherein, E is selected from one or more of Fe and Mn; The sulfate compound includes one or more compounds represented by formula V; Na2Y(SO4)2 • 2H2O Formula Ⅴ Among them, Y is selected from one or more of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V.
10. The sodium ion secondary battery according to claim 9, characterized in that: The layered transition metal oxide includes NaNi m Fe n Mn p O2 compounds, NaNi m Co n Mn p One or more of the O2 compounds, where m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1; The Prussian blue compound includes Na x´ Mn[Fe(CN)6] y´ •z´H2O compound, Na x´ Fe[Fe(CN)6] y´ • one or more of z´H2O compounds, where 0<x´≤2, 0<y´≤1, 0<z´≤20; The phosphate compounds include Na3(VPO4)2F3, Na3(VOPO4)2F, Na2FePO4F, and Na2MnPO4F.
Citation Information
Patent Citations
Low-temperature sodium-ion battery electrolyte with flame-retardant function
CN113555606A
Nonaqueous electrolyte solution and nonaqueous electrolyte secondary battery using the same
JP2017107830A